Alzheimer’s disease: history, ethics and medical humanities in the context of assisted suicide - Braun, Birgit; Demling, Joachim; Loew, Thomas Horst (Philosophy, Ethics, and Humanities in Medicine, 2022)
Introduction: Dementia diseases, especially Alzheimer’s disease (AD), are of considerable importance in terms of social policy and health economics. Moreover, against the background of the current Karlsruhe judgement on the legalisation of assisted suicide, there are also questions to be asked about medical humanities in AD. Methodology: Relevant literature on complementary forms of therapy and prognosis was included and discussed. Results: Creative sociotherapeutic approaches (art, music, dance) and validating psychotherapeutic approaches show promise for suitability and efficiency in the treatment of dementia, but in some cases still need to be scientifically tested. Biomarker-based early diagnosis of dementia diseases is increasingly becoming a subject of debate against the background of the Karlsruhe ruling. Discussion: Needs-oriented and resource-enhancing approaches can make a significant contribution to improving the quality of life of people with dementia. The discussion on the issue of “assisted suicide” should include questions of the dignity and value of a life with dementia. Outlook: The integrative dementia therapy model can be complemented by a religion- and spirituality-based approach. Appropriate forms of psychotherapy should be scientifically evaluated.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Alzheimer dementia; Assisted suicide; Dignity; Ethics; Integrative dementia therapy model